Case report: Alexander's disease with “head drop” as the main symptom and literature review - Yuan, Yujun; Wu, Qiong; Huo, Liang; Wang, Hua; Liu, Xueyan (Frontiers in Neurology, 2022)
Alexander's disease (AxD) is a rare autosomal dominant hereditary disorder that is caused by the mutations in the GFAP gene, which encodes the glial fibrillary acidic protein (GFAP). This neurogenerative disease has many clinical manifestations, and the onset of disease spans a wide range of ages, from newborns to children, adults, and even the elderly. An overaccumulation of the expression of GFAP has a close causal relationship with the pathogenesis of Alexander's disease. Usually, the disease has severe morbidity and high mortality, and can be divided into three distinct subgroups that are based on the age of clinical presentation: infantile (0–2 years), juvenile (2–13 years), and adult (>13 years). Children often present with epilepsy, macrocephaly, and psychomotor retardation, while adolescents and adults mainly present with muscle weakness, spasticity, and bulbar symptoms. Atonic seizures are a type of epilepsy that often appears in the Lennox–Gastaut syndrome and myoclonic–astatic epilepsy in early childhood; however, the prognosis is often poor. Atonic episodes are characterized by a sudden or frequent reduction in muscle tone that can be local (such as head, neck, or limb) or generalized. Here, we report a 4-year-old girl whose main symptoms were intermittent head drop movements, which could break the frontal frame and even bleed in severe conditions. A video-encephalography (VEEG) showed that the nodding movements were atonic seizures. A head magnetic resonance imaging (MRI) revealed abnormal signals in the bilateral paraventricular and bilateral subfrontal cortex. The gene detection analyses indicated that the GFAP gene exon 1 c.262 C>T was caused by a heterozygous mutation, as both her parents were of the wild-type. The girl had no other abnormal manifestations except atonic seizures. She could communicate normally and go to kindergarten. After an oral administration of sodium valproate, there were no atonic attacks. Although epilepsy is a common symptom of Alexander's disease, atonic seizures have not been reported to date. Therefore, we report a case of Alexander's disease with atonic seizures as the main symptom and provide a review of the literature.